A reliable seamless handoff scheme based on enhanced MADM methods. (2017) - Preethi, G. Ananthachari; Chandrasekar, C.
One of the prominent issues these days is the support for heterogeneous handoff. Different types of network come with high end data rates for rapid data transmission. The issues still develops when the distance and the call duration being long for a mobile device. Frequent change of base-station in a mobile terminal causes the signal drop in which it is termed as a call drop in a mobile device. The process is known as handoff breakdown. To prevent the handoff failures we choose multiple attribute decision-making methods for selecting best network for handoff decision. A reliable handoff scheme is implemented for overcoming the handoff predicament. Two novel methods known as enhanced ordered weighted average method (E-OWA) and enhanced grey relational analysis method (E-GRA) were implemented and the results were compared under the reliable handoff scheme. Parameters such as data rate, packet loss, velocity, bandwidth, dwell time and jitter were used to analyse the service provider's performance.